Serotonin selective reuptake inhibitors and suicide risk in a Portuguese adolescent sample - Duarte, Nuno (2023)
Background: The adolescent population is at high risk for depressive disorders, and suicide is a leading cause of death in this age group worldwide. Selective serotonin reuptake inhibitors (SSRIs) remain the only approved pharmacological approach, despite concerns about suicidality. Objectives: This study aimed to understand the relationship between antidepressant use and suicidality in an adolescent population from an Adolescent Psychiatric unit in Lisbon, Portugal. Methods: A total of 296 medical reports of adolescent patients with depressive symptoms in psychiatric follow-up at the considered unit were reviewed. Two demographically and clinically similar samples were obtained, one exposed to SSRI treatment and one control group. Results: A risk of suicide attempt of 0.006 was found in the group exposed to SSRIs versus 0.025 in the control group, corresponding to a relative risk of suicidality of 0.248. This difference did not reach statistical significance, despite a Bayes factor of 4.57 and a Pearson’s r of -0.078. Conclusions: The study results suggest that SSRIs do not increase the risk of suicide attempt in adolescents with depressive symptoms.